If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying cx + c(2) = 5c(2) + -7cx Reorder the terms for easier multiplication: cx + 2c = 5c(2) + -7cx Reorder the terms: 2c + cx = 5c(2) + -7cx Reorder the terms for easier multiplication: 2c + cx = 5 * 2c + -7cx Multiply 5 * 2 2c + cx = 10c + -7cx Solving 2c + cx = 10c + -7cx Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-10c' to each side of the equation. 2c + -10c + cx = 10c + -10c + -7cx Combine like terms: 2c + -10c = -8c -8c + cx = 10c + -10c + -7cx Combine like terms: 10c + -10c = 0 -8c + cx = 0 + -7cx -8c + cx = -7cx Add '7cx' to each side of the equation. -8c + cx + 7cx = -7cx + 7cx Combine like terms: cx + 7cx = 8cx -8c + 8cx = -7cx + 7cx Combine like terms: -7cx + 7cx = 0 -8c + 8cx = 0 Factor out the Greatest Common Factor (GCF), '8c'. 8c(-1 + x) = 0 Ignore the factor 8.Subproblem 1
Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0Subproblem 2
Set the factor '(-1 + x)' equal to zero and attempt to solve: Simplifying -1 + x = 0 Solving -1 + x = 0 Move all terms containing c to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + x = 0 + 1 x = 0 + 1 Combine like terms: 0 + 1 = 1 x = 1 Add '-1x' to each side of the equation. x + -1x = 1 + -1x Combine like terms: x + -1x = 0 0 = 1 + -1x Simplifying 0 = 1 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
c = {0}
| 5x+3(x+14)=200 | | 2z+9.775-7z=-5.15 | | p=x+c+b | | 3x+4yi=12+8i | | 5x+4=5(x+7) | | -3+9=m-1 | | 4x-1+2x+1=8x-4 | | 20x+5x-15x=90 | | -32-3.6f=-17 | | 5(1-2b)=-37-4b | | -(2z+7)=4-z | | 5x+.50=x | | -32z=-39 | | n+(n+1)+(n+2)=-93 | | 3x-9=-5x+15 | | 6/7y-2=1/7y+8 | | 14x^5-24x^4= | | 137x-150x+600-7x=0 | | 2x^2-4.6x+1.2=0 | | 4+3n=-26 | | 3x^2+kx+3=0 | | .50+5x=1+x | | 5x-2+6=6x-7 | | 16(y-8)+6y=2y-9(30) | | 3(x+5)=7(x+1) | | 2(y^2+2y)-(y^2-y)= | | -8(7m+14)+1=-7(8m+1) | | d=18-11 | | .75x-.33=.66x+.20 | | 7v-6*3+9v+7*6=26 | | x+4.9=12.6 | | 5(x+1)-(x-18)=11 |